Elites rioplatenses del siglo XIX : Biografías, representaciones, disidencias y fracasos - Troisi Melean, J. (Comp.); Barcos, M. F. (Comp.) (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2023)
Rioplatenses elites of the 19th century : Biographies, representations, dissidences and failures